Degradation effect of Ce/Al2O3 catalyst on pyrolysis volatility of pine. (December 2020) - Pang, Yunji; Wu, Yuting; Chen, Yisheng; Luo, Fuliang; Chen, Junjun
Abstract: Supported catalysts were prepared with CeCl3 and CeO2 as active components, the catalytic degradation of volatiles from pine particle pyrolysis was studied. Activated alumina was used as the carrier of CeO2 and CeCl3 to prepare CeO2 /Al2 O3 and CeCl3 /Al2 O3 catalysts. Experimental results show that the two catalysts can effectively reduce the yield of pyrolysis liquid-phase products and markedly increase the yield of gas-phase products. Compared with no catalyst, the liquid product yield decreased by 25.69% and the pyrolysis gas yield increased by 29.48% at a pyrolysis temperature of 650 °C by using CeO2 /Al2 O3 catalyst. The active components in CeO2 reduced the volume fraction of Cn Hm in pyrolysis gas and increased the volume fraction of H2 . Under the catalysis of CeCl3 /Al2 O3, the CO content and the low calorific value of the product gas increases. The addition of the two catalysts cracked the oxygen-containing functional groups in the tar to various extents, reducing the tar yield and increasing the pyrolysis gas yield. For the simple reduction of tar yield in pyrolysis gas, the catalytic cracking effect of CeO2 /Al2 O3 catalyst was better than that of CeCl3 /Al2 O3 catalyst, and CeCl3 /Al2 O3 catalyst should be selected when degrading tar while obtaining a relatively high low heating value.